Hukum Sebagai Instrumen Kebijakan Publik: Studi Peran Hukum dalam Pengembangan Lembaga Keuangan Syariah (LKS) - Adi , Putra Silachi Agusta (Kartika: Jurnal Studi Keislaman, 2021)
The aim of this study is to analyze the relationship between law and public policy, which the author formulates in the title: Law as a Public Policy Instrument: Study of the Role of Law in the Development of Sharia Financial Institutions. The research method used in this research is a literature review. The results of this study show that Sharia Financial Institutions development policies and statutory regulations have supported the development of Sharia Financial Institutions. If observed, after the reform period, the government has passed several laws and regulations related to Sharia Financial Institutions, including Law no. 21 of 2008 concerning Sharia Banking and Law no. 1 of 2013 concerning Microfinance Institutions. Law is needed so that state and government policies can obtain an official form that is binding and can be enforced by the public. Juridical support is the basis for determining a policy. This basis comes from positive law and Islam.